Analysis of natural radionuclides in coal, slag and ash in coal-fired power plants in Serbia - Janković M.M.; Todorović D.J.; Nikolić J.D. (Journal of Mining and Metallurgy. Section B: Metallurgy)
The radioactivity monitoring in the “Nikola Tesla”, “Kolubara”, “Morava” and “Kostolac” coal-fired power plants was performed by the Radiation and Environmental Protection Laboratory, Vinča Institute of nuclear sciences in the period 2003-2010. Monitoring included the analysis of soil, water, flying ash, slag, coal and plants. This paper presents the results of the radioactivity analysis of coal, ash and slag samples. Naturally occurring radionuclides 226Ra, 232Th, 40K, 235U, 238U, and 210Pb as well as the man-made radionuclide 137Cs were determined by gamma spectrometry using HPGe detector. The concentrations of pairs of radionuclides were statistically tested to determine the correlation between them. Based on the obtained results, health effect due to the activity of these radionuclides was estimated via radium equivalent (Raeq), external hazard index (Hex), external gamma absorbed dose rate () and annual effective dose.